Smartphone and Generative AI Based Workflow for Fashion MSME Catalogs - Raynald Alfian Yudisetyanto; Agus Setiawan Fazry; Daru Tunggul Aji (Sanggitarupa, 2026)
This research is motivated by the rapid development of generative Artificial Intelligence (AI), which has transformed the production process of commercial photography from conventional shooting practices into a generative visual workflow system. The study aims to design a smartphone-based commercial photography workflow integrated with generative AI for the production of fashion product catalogs for MSMEs on e-commerce platforms. This study employs a qualitative approach using a case study method through observations of visual production processes, workflow experiments, in-depth interviews, and comparative analysis of image transformations from initial smartphone photographs into AI-generated catalog visuals. The findings reveal that the integration of smartphone photography and generative AI creates a visual production workflow that is more efficient, flexible, and cost-effective for e-commerce catalog production. AI functions not only as a visual editing tool but also as a generative system capable of constructing commercial photography simulations, including lighting arrangements, visual backgrounds, model poses, and aesthetic product details through prompt-based processes. The study also indicates a shift in the role of photographers from image producers to visual directors within the contemporary digital photography workflow. This research proposes an adaptive workflow model as an alternative approach to visual catalog production for MSMEs in the AI-driven digital commerce era.